A New Global Optimization Algorithm for Solving Generalized Geometric Programming. (18th January 2011) - Liu, San-Yang; Wang, Chun-Feng; Liu, Li-Xia
Abstract : A global optimization algorithm for solving generalized geometric programming (GGP) problem is developed based on a new linearization technique. Furthermore, in order to improve the convergence speed of this algorithm, a new pruning technique is proposed, which can be used to cut away a large part of the current investigated region in which the global optimal solution does not exist. Convergence of this algorithm is proved, and some experiments are reported to show the feasibility of the proposed algorithm.